Parenting in the bapukung tradition - Rahmawati, Siti; Prihartanti, Nanik; Purwandari, Eny (Indigenous, 2022)
Abstract. South Kalimantan has local culture and wisdom regarding child care, especially in putting children to sleep. This tradition has been passed down from generation to generation until now, namely the unique and extreme Bapukung tradition. The purpose of this research is to describe how to raise children with the Bapukung Tradition and why this tradition is used for child care. This research uses a qualitative method with an ethnographic approach (which describes the authentic views of participants objectively), data collection techniques using purposive sampling techniques using interviews, observation, and documentation. The participants were 15 caregivers from five TPA-PAUD in Tabalong Regency, South Kalimantan with the following characteristics: 1) professional babysitters; 2) aged 22–70 years; 3) junior high school education; and 4) Banjarese and non-Banjarese. Analysis of the data used through the Nvivo program The findings in this study are: 1) The bapukung tradition is the urang Bahari tradition (in the past), putting the child to sleep in a seated position, covered with a swing cloth, tied and rocked with the aim of overcoming a fussy child, regulating the child's sleep pattern, sleeping peacefully and For a long time, the child is safe as in a hug and comfort. The bapukung process is accompanied by a touch of love, hums of tauhid sentences, prayers, and advice, all recorded in the child's memory; 2) Children benefit from warm bodies, strong necks, backbones, and healthy bodies free of coughs, runny noses, and shortness of breath, while caregivers benefit from being able to work while being busy, not stressed, comfortable, and calm in parenting. The bapukung tradition has an impact on the psychology of children and caregivers and affects the child's physiology, so this tradition must be preserved by the people of South Kalimantan and can be adopted by the Indonesian people as a solution to child care Keywords: childcare; Bapukung tradition; parenting.